How do different cigarette design features influence the standard tar yields of popular cigarette brands sold in different countries?. (2nd September 2008) - O'Connor, R J; Hammond, D; McNeill, A; King, B; Kozlowski, L T; Giovino, G A; Cummings, K M
Abstract : Objectives: To examine the associations among cigarette design features and tar yields of leading cigarette brands sold in the United States, Canada, Australia and the United Kingdom. Methods: Government reports and numbers listed on packs were used to obtain data on International Organization for Standardization (ISO)/Federal Trade Commission (FTC) yields for the tar of 172 cigarette varieties sold in the United States, Canada, Australia and the United Kingdom. We used standardised methods to measure the following 11 cigarette design parameters: filter ventilation, cigarette pressure drop, filter pressure drop, tobacco rod length, filter length, cigarette diameter, tipping paper length, tobacco weight, filter weight, rod density and filter density. Results: Filter ventilation was found to be the predominant design feature accounting for the variations between brands in ISO/FTC tar yields in each of the four countries. After accounting for filter ventilation, design parameters such as overwrap length, tobacco weight and rod density played comparatively minor roles in determining tar yields. Conclusions: Variation in ISO/FTC tar yields are predicted by a limited set of cigarette design features, especially filter ventilation, suggesting that governments should consider mandatory disclosure of cigarette design parameters as part of comprehensive tobacco product regulations.